Integration of local wisdom through Enculturation-Assimilation-Acculturation (EAA): A solution to enhance problem-solving skills - Ika Nurani Dewi; Baiq Muli Harisanti; S. Sumarjan (University of Muhammadiyah Malang, 2021)
The 21st-Century learning has been widely associated with problem-solving skills in a global perspective but not much related to local wisdom, even though local perspectives are also needed in adapting people's daily social lives. The purpose of this research was to analyze the effectiveness of Enculturation-Assimilation-Acculturation (EAA) model in enhancing problem-solving skills in learning science. This is pre-experimental research by using one group pretest and post-test design. The samples used were 140 students from two junior high schools in West Nusa Tenggara: (1) SMPN 2 Gunung Sari and (2) SMPN 3 Lingsar. Data collection using a problem-solving test refers to Curtis & Denton. Local wisdom integrated into EAA is the culture of the Sasak Tribe, including Bau Nyale, GORA rice, and awiq-awiq. The analysis data was done using Paired t-test/Wilcoxon test, N-gain, Tukey, ANOVA, and Kruskal-Wallis. The results showed that the integrated EAA model effectively enhances problem-solving skills (sig 0.001). The level of increase is medium, the average level of increase in the six groups is significantly different, and there are differences in learning outcomes of problem-solving skills. Therefore, it can be concluded that the integrated EAA teaching model effectively enhances students' problem-solving skills. The results of this study imply that the EAA integration model can be used as an alternative to overcome the low scientific creativity and responsibility of students in West Nusa Tenggara.